Resilience of temporal processing to early and extended visual deprivation. (September 2021) - Ye, Jie; Gupta, Priti; Shah, Pragya; Tiwari, Kashish; Gandhi, Tapan; Ganesh, Suma; Phillips, Flip; Levi, Dennis; Thorn, Frank; Diamond, Sidney; Bex, Peter; Sinha, Pawan
Abstract: Early visual deprivation is known to have profound consequences on the subsequent development of spatial visual processing. However, its impact on temporal processing is not well characterized. We have examined spatial and temporal contrast sensitivity functions following treatment for early and extended bilateral visual deprivation in fifteen children born with congenital cataracts in rural India. The results reveal a marked difference in post-treatment spatial and temporal sensitivities. Whereas spatial processing in newly sighted children is significantly impaired relative to age-matched controls, temporal processing exhibits remarkable resilience and is comparable to that in the control group. This difference in spatial and temporal outcomes is especially surprising given our computational analyses of video sequences which indicate a strong linkage between the spatial and temporal spectral content of natural visual inputs. We consider possible explanations for this discrepancy.